2019
DOI: 10.3390/math7030283
|View full text |Cite
|
Sign up to set email alerts
|

Distance Degree Index of Some Derived Graphs

Abstract: Topological indices are numerical values associated with a graph (structure) that can predict many physical, chemical, and pharmacological properties of organic molecules and chemical compounds. The distance degree (DD) index was introduced by Dobrynin and Kochetova in 1994 for characterizing alkanes by an integer. In this paper, we have determined expressions for a DD index of some derived graphs in terms of the parameters of the parent graph. Specifically, we establish expressions for the DD index of a line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Yan et al [11] de ned the new graphs called as subdivided graph S(G), vertex-total graph R(G), edge-total graph Q(G) and total graph T(G) with the help of the subdivision-related operations S, R, Q and T respectively. Xu et al [12] have determined the degree distance index of the derived graphs. Bahadur et al [13] have determined Gutman index of derived graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [11] de ned the new graphs called as subdivided graph S(G), vertex-total graph R(G), edge-total graph Q(G) and total graph T(G) with the help of the subdivision-related operations S, R, Q and T respectively. Xu et al [12] have determined the degree distance index of the derived graphs. Bahadur et al [13] have determined Gutman index of derived graphs.…”
Section: Introductionmentioning
confidence: 99%
“…Topological index is a part of chemical graph theory which correlates the physicochemical properties such as freezing point, boiling point, melting point, infrared spectrum, electronic parameters, viscosity, and density of the underlying chemical graphs. e reader can find bulk of papers on topological indices which have been in print so far [1][2][3][4][5].…”
Section: Introduction and Applicationsmentioning
confidence: 99%
“…where d u denotes the degree of a vertex u. Recent studies on Zagreb indices and distance based indices may be found in Liu et al (2019), Siddiqui (2020), and Xu et al (2019). In 1998, ABC-index were introduced by Estrada et al (1998).…”
Section: Introductionmentioning
confidence: 99%